SEMANGAT: Realizing a healthy, independent, enterprising and optimistic community at LKSA Muhammadiyah Nanggulan Orphanage, Kulon Progo - Zahro Varisna Rohmadani; Avininda Dewi Nindiasari; Fajar Satriya Segarawasesa; Tri Winarsih (Universitas Muhammadiyah Magelang, 2022)
This community service program's main goal is to assist partners become a Healthy, Independent, Enterprising, and Optimistic (SEMANGAT). Despite the uncomfortable things that have happened in their lives at the LKSA Muhammadiyah Nanggulan Orphanage, Kulon Progo. The program was carried out in several steps, including: (1) counseling and education on healthy lifestyles; (2) psychological assessment to assess the potential intelligence, interests, and talents; (3) hypnotherapy to reduce anxiety and increase optimism; (4) teaching how to make drinks with aloe vera; and (5) entrepreneurial training through online branding and marketing as well as bookkeeping training. This program's outcomes include partners understanding how to maintain and improve their health, the intellectual potential of their talents and interests, less anxious and more optimistic, able to make drinks with aloe vera, and understand how to brand and market online, as well as to record profit and loss.